2009
DOI: 10.1002/adma.200900469
|View full text |Cite
|
Sign up to set email alerts
|

Stray‐Field‐Induced Actuation of Free‐Standing Magnetic Shape‐Memory Films

Abstract: Magnetic shape-memory (MSM) alloys, such as NiMnGa, [1] reach maximum strains of close to 10% in single crystals. [2] This exceeds the strain obtainable from piezoelectric or magnetostrictive materials, currently used in actuators, by more than one order of magnitude, and opens new opportunities for applications. Advanced materials have been developed based on new compositions [3][4][5] or on innovative routes of fabrication resulting in foams, [6] fibers, [7] textured polycrystals, [8] or composites.[9] Thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…A detailed analysis revealed that this is due to an alternative thermal actuation mode, only possible in thin magnetic shape memory films. 17 Since variants with a perpendicular aligned easy magnetization axis are energetically disfavored due to the high stray-field energy, this effect was called stray-field-induced microstructure ͑SFIM͒. In this letter we show that these freestanding films also exhibit a magnetically induced martensitic transition.…”
mentioning
confidence: 84%
“…A detailed analysis revealed that this is due to an alternative thermal actuation mode, only possible in thin magnetic shape memory films. 17 Since variants with a perpendicular aligned easy magnetization axis are energetically disfavored due to the high stray-field energy, this effect was called stray-field-induced microstructure ͑SFIM͒. In this letter we show that these freestanding films also exhibit a magnetically induced martensitic transition.…”
mentioning
confidence: 84%
“…Actuation mechanism Reference Magnetic field-induced reorientation (MIR) of martensite Magnetic shape memory (MSM) actuation [4] Temperature gradient-induced martensitic transformation Single phase boundary actuation [34] Thermally induced ferromagnetic transition and martensitic transformation Bidirectional magnetostatic and thermoelastic actuation [35] Thermally induced metamagnetic transition Thermomagnetic actuation [36] Magnetic stray-field-induced microstructure Magnetic stray-field induced actuation [37] …”
Section: Coupling Effectmentioning
confidence: 99%
“…Epitaxial FSMA films show another actuation mechanism based on the magnetic stray-field-induced microstructure [37]. When transforming a ferromagnetic austenite film to the martensite phase, variants with their easy axis in the film plane are preferentially formed in order to avoid magnetostatic energy contributions.…”
Section: Magnetic Stray-field Actuationmentioning
confidence: 99%
“…The MIR effect enables contactless control of large deformations at relatively large bandwidths, which are important prerequisites for applications in small space [6]. Recently, also other mechanisms for FSMA microactuation have been explored such as the induction of phase transformation in Ni-Mn-Ga thin films under high magnetic fields (magnetically induced martensite, MIM) [7,8], the antagonism of thermally induced shape recovery force and ferromagnetic attraction force in a magnetic field gradient [9][10][11], or utilizing a film's magnetic stray field energy to induce a preferential variant orientation [12]. Recent efforts mostly concentrate on the development of FSMA microactuators based on the MIR effect since MIR does not require a phase transformation, which has advantages in terms of power requirements and actuation frequencies.…”
Section: Introductionmentioning
confidence: 99%